2020
DOI: 10.1101/2020.10.13.337899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SQ3370 Activates Cytotoxic Drug via Click Chemistry at Tumor and Elicits Sustained Responses in Injected & Non-injected Lesions

Abstract: While systemic immuno-oncology therapies have shown remarkable success, only a limited subset of patients benefit from them. Our Click Activated Protodrugs Against Cancer (CAPAC™) Platform is a click chemistry-based approach that activates cancer drugs at a specific tumor with minimal systemic toxicity. CAPAC Platform is agnostic to tumor characteristics that can vary across patients and hence applicable to several types of tumors. We describe the benefits of SQ3370 (lead candidate of CAPAC) to achieve systemi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Development of controlled drug delivery by means of Tz-triggered decaging of TCO-drug conjugates or vice versa (click-to-release) makes this chemistry even more attractive. 24,[34][35][36] Recently, we performed a systematic study of the relationship between the physicochemical properties of Tzs and their in vivo click performance in a colon tumor model. This study revealed that only hydrophilic Tzs with fast click kinetics were suitable for pretargeted imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Development of controlled drug delivery by means of Tz-triggered decaging of TCO-drug conjugates or vice versa (click-to-release) makes this chemistry even more attractive. 24,[34][35][36] Recently, we performed a systematic study of the relationship between the physicochemical properties of Tzs and their in vivo click performance in a colon tumor model. This study revealed that only hydrophilic Tzs with fast click kinetics were suitable for pretargeted imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3] Very recently, bioorthogonal chemistry has entered Phase 1 clinical trials, with Tz/TCO-reactions currently being tested in humans, aiming for locally restricted prodrug activation to improve the selectivity of chemotherapeutics. [9][10] In recent years, a variety of differently substituted tetrazines has been used for bioorthogonal reactions and in vivo chemistry, including bis-alkyl-substituted Tz, [11][12][13][14][15] alkyl-aryl-Tz, [16][17][18][19] mono-alkyl-Tz [20] (alkyl-H-Tz) as well as highly reactive bisheteroaryl [21][22] and mono-aryl [23][24][25][26] derivatives (aryl-H-Tz). These applications have motivated and fueled the development of advanced procedures for the synthesis of tetrazine scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] A targeted drug delivery system based on this cycloaddition is currently in phase 1 clinical studies. 12,13 Commonly used tetrazines include mono-and di-substituted derivatives with alkyl or aryl groups. [14][15][16][17] Due to the inverse electrondemand nature of the initial, rate limiting [4+2] cycloaddition, electron withdrawing substituents increase reactivity.…”
Section: Introductionmentioning
confidence: 99%